2022
DOI: 10.52082/jssm.2023.1
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Surface Electromyography for the Evaluation of Muscle Activity during Front Crawl Swimming: A Systematic Review

Abstract: This systematic review is aimed to provide an up-to-date summary and review on the use of surface electromyography (sEMG) in evaluating front crawl (FC) swim performance. Several online databases were searched by different combinations of selected keywords, in total 1956 articles were retrieved, and each article was assessed by a 10-item quality checklist. 16 articles were eligible to be included in this study, and most of the articles were evaluating the muscle activity about the swimming phases and focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…In addition to the evaluation in terms of activation, several studies have focused on the assessment through dynamic and static force indicators [ 24 , 25 ]. In addition, the assessment of asymmetries in relation to muscle activation [ 26 , 27 , 28 ] and static strength indicators [ 9 , 29 ] has been widely used.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the evaluation in terms of activation, several studies have focused on the assessment through dynamic and static force indicators [ 24 , 25 ]. In addition, the assessment of asymmetries in relation to muscle activation [ 26 , 27 , 28 ] and static strength indicators [ 9 , 29 ] has been widely used.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the muscles involved in swimming through electromyographic (EMG) analysis has helped deepen our understanding of how athletes maintain peak performance even in the face of muscle fatigue [23]. Recent research [28][29][30][31][32][33][34][35] has revealed the central role of specific muscles in maintaining speed and performance under fatigue conditions. For example, the latissimus dorsi (LD), triceps brachii (TB), and pectoralis major (PM) muscles often exhibit dynamic and strategic adaptations [30,32].…”
Section: Introductionmentioning
confidence: 99%